2022
DOI: 10.1021/acsaem.2c00828
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Synergistic Effect of g-C3N4/Graphite Heterostructures for Boosting Sodium Ion Storage with Long Cycle Stability

Abstract: Sodium-ion batteries (SIBs) have attracted significant attention as promising next-generation energy storage devices. However, the research and development of SIBs are still in their infancy due to the lack of suitable high-performance anode materials. As a commercial anode material for lithium-ion batteries (LIBs), graphite often shows a low sodium storage capacity. Herein, a graphite heterojunction material was prepared through a facile ball-milling method. During the ball-milling process, a defect-enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated that the introduction of conductive carbon materials into composite heterojunctions with C x N y can induce unique chemical terminal bonds, improving electrical conductivity and mechanical properties. 126,128 Successful synthesis of This journal is © The Royal Society of Chemistry 2024 C x N y /conductive carbon heterojunctions, such as g-C 3 N 4 /reduced graphene oxide (rGO), 126,129 g-C 3 N 4 /graphene, 130,131 g-C 3 N 4 /Graphite, 132 and g-C 3 N 4 /carbon nanotubes (CNTs), [133][134][135] have been achieved and utilized in lithium batteries, lithium-sulfur batteries, and sodium batteries.…”
Section: Conductive Carbon/c X N Ymentioning
confidence: 99%
“…Several studies have demonstrated that the introduction of conductive carbon materials into composite heterojunctions with C x N y can induce unique chemical terminal bonds, improving electrical conductivity and mechanical properties. 126,128 Successful synthesis of This journal is © The Royal Society of Chemistry 2024 C x N y /conductive carbon heterojunctions, such as g-C 3 N 4 /reduced graphene oxide (rGO), 126,129 g-C 3 N 4 /graphene, 130,131 g-C 3 N 4 /Graphite, 132 and g-C 3 N 4 /carbon nanotubes (CNTs), [133][134][135] have been achieved and utilized in lithium batteries, lithium-sulfur batteries, and sodium batteries.…”
Section: Conductive Carbon/c X N Ymentioning
confidence: 99%
“…Numerous 2D materials, such as graphene, reduced graphene oxide (RGO), graphitic carbon nitride (g-C 3 N 4 ), and MXene, have been considered as potential candidates for both lithium-ion and sodium-ion battery anodes. [2][3][4][5][6][7] Among them, a novel pentagonal material proposed by Zhang et al, 8 pentagraphene, has attracted the interest of many researchers due to its fascinating pentagonal structure. A large number of studies have been conducted to design new members of the pentagonbased system, such as CN 2 , BN 2 , B 2 C, SiC 2 , and NiS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[22] Notably, the atomically smooth interface with highly matched lattice in the homophase junction leads to a less-defective and abrupt interface and provides the smooth interfacial charge separation and transfer path. [23] Motivated by the advantages of interfacial chemical bond and homophase junction strategy, herein, taking 2D carbon nitride nanosheets (denoted as CN) [24][25][26][27][28] as a model light absorber, a brookite TiO 2 homophase junction (B N -B R ), formed by nanoparticle brookite TiO 2 (B N ) and rod brookite TiO 2 (B R ) was used as effective electron transport layer to be anchored on CN (denoted as B N -B R /CN). The brookite TiO 2 , which exhibits a monoclinic C2/m structure comprised of edge and cornersharing TiO 6 octahedra, have layered structures with lower packing density and open channels.…”
Section: Introductionmentioning
confidence: 99%